2024
DOI: 10.1021/acsanm.3c04403
|View full text |Cite
|
Sign up to set email alerts
|

Facile Fabrication of UV Photodetectors Using Spin-Coating Flame-Synthesized ZnO Nanoparticles

Xiaohu Chen,
Shujuan Huang,
Noushin Nasiri

Abstract: A facile and direct spin-coating technique was employed in the synthesis of UV photodetectors utilizing flame-made, highly crystalline ZnO nanoparticles (NPs) deposited on glass substrates. The morphological and microstructural analysis revealed that this nonchemical reaction-based spincoating approach can generate homogeneous ZnO thin films with tunable thickness, possessing an average porosity of 80%, which is significantly higher compared to conventional spin-coated films. With the coating cycles increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 70 publications
3
2
0
Order By: Relevance
“…The flame-sprayed ZnO films exhibit near-ohmic behavior, as depicted in Figure S11, indicating a low-resistance contact with the Pt-interdigitated electrodes. This observation aligns with our prior findings on flame-synthesized metal oxide thin films. ,,,, Figure a shows the spectral responsivity of the photodetectors as a function of the illumination wavelength from 275 to 850 nm under a light density (LD) of 25 μW/cm 2 and an applied bias of 0.5 V. Responsivity ( R λ ), as defined, represents the ratio of the photocurrent generated by a device per unit area to the incident light power at a specific wavelength (λ). This can be calculated as R λ = Δ I / P , where Δ I and P are the photocurrent density and incident light density, respectively.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The flame-sprayed ZnO films exhibit near-ohmic behavior, as depicted in Figure S11, indicating a low-resistance contact with the Pt-interdigitated electrodes. This observation aligns with our prior findings on flame-synthesized metal oxide thin films. ,,,, Figure a shows the spectral responsivity of the photodetectors as a function of the illumination wavelength from 275 to 850 nm under a light density (LD) of 25 μW/cm 2 and an applied bias of 0.5 V. Responsivity ( R λ ), as defined, represents the ratio of the photocurrent generated by a device per unit area to the incident light power at a specific wavelength (λ). This can be calculated as R λ = Δ I / P , where Δ I and P are the photocurrent density and incident light density, respectively.…”
Section: Resultssupporting
confidence: 87%
“…An intriguing observation is the progressive augmentation of photogenerated currents with an increasing number of on/off cycles, consistent with extant literature. , Notably, during each UV exposure iteration, a subset of charge carriers, comprising electrons or holes, may become ensnared within defect states embedded within the ZnO matrix. If these ensnared carriers remain incompletely liberated during off cycles, they amass across successive iterations.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Photodetector (PD) devices, which are magnificent tools for the conversion of optoelectronic signals, have been implemented in optical communications, biological imaging, and environmental surveillance . In recent years, PD devices based on metal-oxide semiconductors, especially zinc oxide (ZnO) nanostructures, have been widely used due to their beneficial properties such as ease of manufacturing, morphology and defect control, eco-friendly nature, and excellent stability. , Low-temperature synthesis can provide various morphologies on nano- and microscales, making ZnO a promising material in optoelectronic and photoelectrochemical devices. Thus, there is a great variety of ZnO-based photoelectrodes and PD devices bearing various nanostructures, such as nanowires (NWs), nanorods (NRs), , nanotubes (NTs), , nanodisks (NDs), nanosheets (NSs), and nanoflowers (NFs) . Among all ZnO nanostructures, 3D ZnO nanostructures have attracted great attention due to their striking features such as a high surface area, enhanced optical absorption owing to multiple reflections and scattering, and better permeability.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, most of the literature reports have agreed that pristine ZnO-based PDs exhibit slow response time because of the atmospheric adsorbates such as oxygen and water molecules, creating charge trap states on the surface . Therefore, a great effort has been devoted to improving the optoelectronic and photodetection properties of ZnO. The most common routes to enhance the photoresponse performance of ZnO-based PDs are doping of metals and preparing nanocomposites. In our previous research, flexible pristine and Mn-doped ZnO NRs (Mn/ZnO NR)-deposited MSM-type PDs were thoroughly investigated in terms of photoresponse time and detectivity . We observed that the photodetection parameters such as detectivity ( D *), responsivity ( R ), and response/recovery time have been improved by the Mn dopant.…”
Section: Introductionmentioning
confidence: 99%